How big is a pig? - Beaton, Clare (Cambridge, MA : Barefoot Books, 2000)
Contrasts animals in the barnyard, including clean and dirty geese, fat and thin cows, and big and small pigs.
Keywords: Domestic animals; English language; Stories in rhyme